Study on Sediment Disaster and Resources Management in Mt.Merapi Area - Jazaul Ikhsan, Masaaru Fujita, Hiroshi Takebayashi (International Journal of Erosion Control Engine, 2010)
in this paper, we discussed about related sediment disaster mitigation and sediment resouces management in Mt.Merapi Area